An innovative approach to fabricate a thermosensitive melatonin‐loaded conductive pluronic/chitosan hydrogel for myocardial tissue engineering. Issue 18 (25th November 2020) - Torabi, Hadis; Mehdikhani, Mehdi; Varshosaz, Jaleh; Shafiee, Fatemeh
Abstract: This study aimed at designing and fabrication of a novel injectable and thermosensitive melatonin‐loaded pluronic/chitosan hydrogel containing gold nanoparticles (GNPs) and poly glycerol sebacate (PGS) for myocardial tissue engineering. The PGS nanoparticles were used as the melatonin (drug model) carrier. The gelation time, syringeability, stability, and swelling of the hydrogel were scrutinized. Rheological properties, chemical composition, and morphology of the samples were also investigated. The effect of GNPs addition on the electrical conductivity of hydrogel was assessed. The cytotoxicity of hydrogels was assessed through MTT assay in the exposure of H9C2 cells up to 7 days. Scanning electron microscopy was applied to evaluate the morphology of seeded cells. The synthesis parameters of PGS nanoparticles were optimized through which 2.5%w/v of PGS and 1:10 organic phase to aqueous phase (O/A) ratio were found desirable. The optimum hydrogel illustrated 2 min gelation time and was stable up to 20 days with 5% swelling in the first 12 h into phosphate buffered saline. The GNPs with a uniform distribution rendered the hydrogel electrically conductive (1500 μS/cm). According to the MTT assay results, 3.125 μM melatonin was considered as the suitable concentration by which a significant increase in the cell viability was observed. The results exhibited that the prepared hydrogel composed of pluronic/chitosan/GNPs, and 3.125 μM melatonin‐loaded PGS nanoparticles could be applied as a promising scaffold for myocardial tissue engineering. Abstract :